Infância, família e escola: análise dos significados da Infância e dos Direitos da Criança - Lima, Aline Graciele [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This study aimed at analyzing the meanings of Children and Child Rights awarded by the kindergarten children and their educators, parents and teacher. Interest in the subject arose from the participation of the University Extension Project, conducted at the Department of Education, UNESP, Bauru, called The Rights of the Child: ECA in school. Since then, the question arose: to what extent we have visibility of meanings that educators and the child has on the Rights of the Child relating to the specifics of childhood? The research followed the tenets of qualitative research, methodological procedures and adopting the observation in a classroom from kindergarten (K II), semi-structured interview through leisure moments, with the class of aged five years and a questionnaire for family and teacher. The research adopted as reference material, studies of the area of Sociology of Childhood, History of Childhood, Public Policy, Legislation Related to the theme, and an overview of psychogenic to talk about the morality of children. The results showed that parents and caregivers understand childhood as a stage of child development, marked by jokes and fancies, in which the family and the school has an important role in this process. In what concerns the children's rights, there are contradictions in the legal aspects and the situation of children today. The results showed that children's childhood is characterized by recreational activities, and adults are responsible for caring for them. And it comes on the Rights of the Child noted that there is a confusion between rights and duties because they are in a phase of moral heteronomy. The findings indicate the need for wide dissemination on the Statute of Children and Adolescents, especially in preschools in line with families to practice it a new look at childhood, conceiving children as subjects... (Complete abstract click electronic access below)

Este estudo teve como objetivo geral analisar os significados da Infância e dos Direitos da Criança atribuídos por crianças da Educação Infantil e seus respectivos educadores, pais e professora. O interesse pelo tema surgiu da participação do Projeto de Extensão Universitária, realizado no Departamento de Educação, UNESP, campus de Bauru, denominado “Os Direitos da Criança: o ECA na escola”. A partir de então, surgiu à indagação: em que medida temos visibilidade dos significados que educadores e a própria criança tem acerca dos Direitos da Criança relacionados às especificidades da infância? A investigação seguiu os princípios da pesquisa qualitativa, adotando como procedimentos metodológicos a observação em uma turma da Educação Infantil (Jardim II); entrevista semi-estruturada por meio de momentos lúdicos, com a turma de faixa etária de cinco anos e questionário para familiares e professora. A pesquisa adotou como material bibliográfico, estudos da área da Sociologia da Infância, História da Infância, Políticas Públicas, Legislação relacionadas à temática, bem como uma perspectiva da Psicogenética para discorrer acerca da moralidade infantil. Os resultados mostraram que pais e professora entendem a infância como uma etapa de desenvolvimento infantil, marcada por brincadeiras e fantasias, na qual a família e a escola tem importante papel nesse processo. Já no que diz respeito aos direitos infantis, há contradições nos aspectos legais e a situação das crianças na atualidade. Os resultados das crianças mostraram que a infância é caracterizada pelas atividades lúdicas, e os adultos são responsáveis pelo cuidado por elas. E, se tratando dos Direitos da Criança notamos que há uma confusão entre direitos e deveres devido as mesmas estarem numa fase de moral heterônoma. As conclusões apontam a necessidade de uma ampla difusão acerca... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Infância; Direitos das crianças; Sociologia; Educação de crianças; Children; Children’s rights; Sociology; Education